MEKANISME PERAWATAN MESIN BOILER PADA PENGELOLAHAN KELAPA SAWIT DI PT. SIPP - Maesha, Are; Arief, Rudi Kurniawan (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
The palm oil industry in Indonesia has great potential in increasing the country's economic income. This is proven if in 2022 Indonesian palm oil will reach USD 40 billion or IDR 600 trillion. PT Sawit Inti Prima Perkasa (PT. SIPP) is a company engaged in processing FFB (fresh fruit bunches) into CPO (Crude Palm Oil) and PKO (Palm Kernel Oil). However, in its implementation there are still shortcomings in carrying out quality control maintenance. So it requires good utilization of CPO and PKO processing optimization. This research uses mix method research with the aim of finding out how to optimize CPO and PKO processing at PT Sawit Inti Prima Perkasa. The research result show that optimizing the management of CPO and PKO is related to good and comprehensive maintenance. Solving maintenance problems in the oil palm plantation industry will focus on repairing problems in the oil palm plantation industry will focus on repairing problems related to equipment., machinery or infrastructure used in iol palm plantation operations. Successfull productionrequires very thorugh quality control, problem solving and problem which is very useful as a guide in dealing with and finding solutions to problems that can occur in palm iol mills.so that the procces can run smoothly so that thr company does not experience significan losses and can avoid work accident.Keywords: Crude Palm Oil, Palm Kernel Oil, maintenance troubleshooting